Idiom berunsur nama organ tubuh manusia dalam tabloid bola (kajian materi pembelajaran ke-SD-an) - Siti Anafiah; Anang Sudigdo (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine 1) the linguistic form of idioms containing the names of human organs in the Bola tabloid. 2) the types of idioms containing the names of human organs contained in the Bola tabloid. 3) idiom material in elementary Indonesian language learning. This type of research is descriptive. This research is subject to idioms containing the names of human organs contained in the Bola tabloid which was published in January-December 2004. The object of this research is the linguistic form of idioms and the types of idioms containing the names of human organs contained in the Bola tabloid. The research instrument used was the researcher himself. This study also uses a tool, namely a data card. Data collection uses reading and note-taking techniques. The data analysis used is the matching and agih method. The validity of the data is done through intrarater and interater. The results of the study found that the Bola tabloid found language styles from linguistic forms and types of idioms. The linguistic form of idioms has elements of human organs, namely words and phrases. From the type of idiom, it is seen in terms of the closeness of its elements in forming meaning, value content, and references to idiom elements. Idioms are material in the thematic learning of Indonesian content in grade 2 theme 1, sub-theme 1 with KD 3.1 Detailing expressions, invitations, orders, and refusals contained in story texts or songs that describe an attitude of living in harmony, 4.1 Imitating expressions, invitations, orders, and rejection in children's stories or songs with polite language.